Repurposing Approved Drugs for Guiding COVID-19 Prophylaxis: A Systematic Review - Andrade, Bruno Silva; Rangel, Fernanda de Souza; Santos, Naiane Oliveira; Freitas, Andria dos Santos; Soares, Wagner Rodrigues de Assis; Siqueira, Sérgio; Barh, Debmalya; Góes-Neto, Aristóteles; Birbrair, Alexander; Azevedo, Vasco Ariston de Carvalho (Frontiers in Pharmacology, 2020)
The SARS-CoV-2 outbreak originally appeared in China in December 2019 and became a global pandemic in March 2020. This infectious disease has directly affected public health and the world economy. Several palliative therapeutic treatments and prophylaxis strategies have been used to control the progress of this viral infection, including pre- (PrEP) and post-exposure prophylaxis (PEP). On the other hand, research groups around the world are still studying novel drug prophylaxis and treatment using repurposing approaches, as well as vaccination options, which are in different pre-clinical and clinical testing phases. This systematic review evaluated 1228 articles from the PubMed and Scopus indexing databases, following the Kitchenham bibliographic searching protocol, with the aim to list drug candidates, potentially approved to be used as new options for SARS-CoV-2 prophylaxis clinical trials and medical protocols. In searching protocol, we used the following keywords: “Covid-19 or SARS-CoV-2” or “Coronavirus or 2019 nCoV”, “prophylaxis”, “prophylactic”, “pre-exposure” , “COVID-19 or SARS-CoV-2 Chemoprophylaxis”, “repurposed”, “strategies”, “clinical”, “trials”, “anti-SARS-CoV-2”, “anti-covid-19”, “Antiviral ”,“ Therapy prevention in vitro ”,“ in cells ”and“ human testing ”. After all protocol steps, we selected 60 articles that included: 15 studies with clinical data, 22 studies that used in vitro experiments, 7 studies using animal models, and 18 studies performed with in silico experiments. The drugs selected in this review can assist clinical studies and medical guidelines on the rational repurposing of known antiviral drugs for COVID-19 prophylaxis.